Celeng, Metafora Etika Politik Lingkungan:Inspirasi Prosa Lirik Perjalanan Celeng ke Surga, Karya F. Rahardi: Inspirasi Prosa Lirik Perjalanan Celeng ke Surga, Karya F. Rahardi - Dua, Mikhael; Sihotang, Kasdin (Center for Philosophy and Ethics, 2024)
Politic is an inseparable part of human life. Politic is like a double-sided coin; it can be directed positively, meaning it is used to improve the welfare of society in accordance with its essence, or it can become a platform for conflict for power, awakening animalistic instincts through various cunning and dirty means to occupy certain positions. In its implementation, criticism of political life, especially the improper implementation of power, is always present. Such criticism is carried out in various ways. The method of literary writers is one such method. Writers convey criticism of bad power through the use of metaphors. Metaphorical instruments are diverse. One such method is using the name of an animal, the wild boar. Rahardi, a writer, demonstrates this in his book entitled